2011
DOI: 10.1007/s11104-011-0976-7
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal diversity in perennial pastures; responses to long-term lime application

Abstract: Background and aims We investigated the genetic diversity of arbuscular mycorrhizal fungi (AMF) in soils and the roots of Phalaris aquatica L., Trifolium subterraneum L., and Hordeum leporinum Link growing in limed and unlimed soil, the influence of lime application on AMF colonization and the relationship between AMF diversity and soil chemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Therefore, benefits to plant growth associated with mycorrhizal colonization can occur regardless of soil pH, varying according to the species of mycorrhizal fungi (Cavallazzi et al, 2007). Other studies have also shown that lime application in the field can increase mycorrhizal colonization rates (Aliasgharzad et al, 2010;Schneider et al, 2011;Guo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, benefits to plant growth associated with mycorrhizal colonization can occur regardless of soil pH, varying according to the species of mycorrhizal fungi (Cavallazzi et al, 2007). Other studies have also shown that lime application in the field can increase mycorrhizal colonization rates (Aliasgharzad et al, 2010;Schneider et al, 2011;Guo et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Clark (1997) found that maximum enhancement of plant growth in acid soil varied with AMF isolate and soil pH, indicating adaptation of AM isolates to edaphic conditions. Long-term lime application changed soil nutrient availability and increased AMF colonization, but decreased AMF phylotype diversity, implying that soil chemical properties may determine the distribution of AMF in acid soils (Guo et al, 2012). The higher AMF colonization at Al3 compared to Al1 might also be related to the soil available phosphorus concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…300 g spores and sporocarps were obtained. Since the spores isolated from soils were a mixture, the DNA of the soils was extracted and used for AMF identification followed by the method of Guo et al (2012). In total 5 strains were identified, mainly Glomus species (Table 1).…”
Section: Symbiotic Microbesmentioning
confidence: 99%
See 2 more Smart Citations